Evaluation of Customer Satisfaction and Economic Efficiency: A Study of Conventional and Islamic Insurance Industry in Pakistan - Waris, Muhammad Abdullah; Arshad, Zubair; Waqas, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2025)
This study investigates customer satisfaction and economic efficiency within the conventional and Islamic insurance sectors in Pakistan. A modified SERVQUAL model is employed to assess customer satisfaction, utilizing primary data collected from 179 respondents affiliated with the insurance industry. To evaluate economic efficiency, ratio analysis is conducted using secondary data from five conventional and five Islamic insurance companies for the period 2018–2023. The findings reveal no statistically significant difference in customer satisfaction between the two sectors (p > 0.05, Cohen’s d = 0.21). Nonetheless, customers of Islamic insurance demonstrate a higher level of awareness and exhibit a stronger preference for Shar??ah-compliant insurance products compared to their conventional counterparts. Ratio analysis indicates that conventional insurance companies exhibit greater economic efficiency, with average ROA and ROE surpassing Islamic providers (ROA: 2.5% vs. 0.7%; ROE: 5.2% vs. 2.1%). The study recommends that both sectors enhance their service quality and operational efficiency, especially by embracing digital platforms to bridge convenience gaps. Strategic efforts should target potential customers among middle-income, younger, and private sector segments. Islamic insurers must emphasize Shar??ah audit transparency to bolster trust.